Ga. Const. of 1868, art. I, § 14 - (:unkn) unknown (My University, 1868)
Provided that a well-regulated militia was necessary to the security of a free people, the right of the people to keep and bear arms shall not be infringed. However, the legislature has the power to prescribe by law the manner in which arms may be worn.
Keywords: CARRY; GUARANTEED RIGHT